Assessment accuracy of power system frequency security with additional frequency controls in wind turbines. Issue 17 (22nd February 2021) - Steinkohl, Joachim; Wang, Xiongfei; Davari, Pooya; Blaabjerg, Frede
Abstract : Power grids all over the world are nowadays facing high penetrations of renewable power generation. The converter‐based generation units play a major role in system behaviour and operation. Thereby, also the reliability of the power system is impacted in many different aspects. It has to be verified whether the frequency reliability assessment, which is often studied by simulations, is still accurate, every time a new control structure is considered. For this, the number of simulations should not be further increased if possible, in order to keep the computational efforts low. In this study, the authors verify that the assessment outcome will be accurate when the load duration curve (LDC) and wind power curve (WPC) of a system are described well enough. This is shown to be true for different frequency controls, implemented in wind power plants in the system. Besides, the effects of different LDCs and WPCs are analysed, as they can change over time. The used methodology is validated on the IEEE reliability test system (IEEE RTS).